Afirmación cultural y música popular como mecanismos de reivindicación afrocolombianos - Sebastián Olave-Soler (Nuevo mundo - Mundos Nuevos, 2023)
In Colombia, ethnic self-recognition and cultural affirmation have fostered a contestation of the place attributed to populations and symbolic elements of black descent. This article explores the way in which the revaluation of marginalized popular expressions – in particular, the popular music of the Pacific coast – could mean a questioning of the social, cultural and political model of the country.